An Integrated Approach to Facilitate the Training of Methodological Competencies in a Teacher Education Program - Lan Li; Xiongyi Liu; Savilla Banister (Pensa MultiMedia, 2017)
Despite the increasingly recognized importance of research skills of teachers, teacher trainees are often dread of discrete research curricula and deem them as uninteresting and disengaging. This paper presents a model that enables teacher trainees in the Master's program of Education in Classroom Technology at a Mid-western university in the United States to acquire methodological skills in task-based real learning environments. This model employs an escalating process of four phases: Generating Initial Project Ideas, Proposing Research Plans, Collecting and Analyzing Data, and Completing Master's Project and Reporting Findings. Through these four phases, the model aims to streamline core courses and strengthen faculty mentorship to support students' scholarship and creative endeavors. The program evaluation suggests that the model was well received by teacher trainees. Teacher trainees reported positive program experience and highly regarded the academic challenges encountered and the support received in the program. Limitations of the study were discussed and future studies were suggested.